2016
DOI: 10.1038/nphys3670
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for universal relations describing a gas with p-wave interactions

Abstract: Thermodynamics provides powerful constraints on physical and chemical systems in equilibrium. However, non-equilibrium dynamics depends explicitly on microscopic properties, requiring an understanding beyond thermodynamics. Remarkably, in dilute gases, a set of universal relations is known to connect thermodynamics directly with microscopic properties. So far, these "contact" relations have been established only for interactions with s-wave symmetry, i.e., without relative angular momentum.We report measuremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
151
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(158 citation statements)
references
References 59 publications
5
151
0
Order By: Relevance
“…Indeed, in a very recent experiment [3], a steady state with strong p-wave correlations has been achieved in a Fermi gas at a low temperature T = 0.2T F (T F is the Fermi temperature) within a time scale of ∼ 0.5ms. It is thus hopeful that pairing physics can be explored near a p-wave FR at lower temperatures, where a steady state with interesting pairing correlations arXiv:1512.09313v2 [cond-mat.quant-gas] 8 Jan 2016…”
Section: Fig 1 (Color Online) Feshbach Resonances(fr) Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, in a very recent experiment [3], a steady state with strong p-wave correlations has been achieved in a Fermi gas at a low temperature T = 0.2T F (T F is the Fermi temperature) within a time scale of ∼ 0.5ms. It is thus hopeful that pairing physics can be explored near a p-wave FR at lower temperatures, where a steady state with interesting pairing correlations arXiv:1512.09313v2 [cond-mat.quant-gas] 8 Jan 2016…”
Section: Fig 1 (Color Online) Feshbach Resonances(fr) Ofmentioning
confidence: 99%
“…The background color denotes the spin polarization P = (n ↑ − n ↓ )/(n ↑ + n ↓ ). associated with the p + ip pairing symmetry, reminiscent of the A phase in 3 He [16,17].…”
Section: Phase Diagrammentioning
confidence: 99%
See 1 more Smart Citation
“…Besides s-wave, the p-wave interacting atomic gases have also attracted great attention in recent years [8,27], in particular, in view of the very recent explorations of universal properties near p-wave resonance [28][29][30][31]. In this work, we study the interplay of SOC and strong pwave interaction to the short-range and long-range twobody physics.…”
mentioning
confidence: 99%
“…Despite the negligible short-range consequence, SOC can greatly change the long-range (low-energy) scattering properties from near the threshold [13,14,16] to intermediate energy regime [16][17][18]. Moreover, with conventional s-wave models it has been found that SOC can induce shallow molecules [19] and universal trimers [20,21] more easily, and lead to various fascinating many-body phenomena in both bosons and fermions atomic systems [22][23][24][25][26].Besides s-wave, the p-wave interacting atomic gases have also attracted great attention in recent years [8,27], in particular, in view of the very recent explorations of universal properties near p-wave resonance [28][29][30][31]. In this work, we study the interplay of SOC and strong pwave interaction to the short-range and long-range twobody physics.…”
mentioning
confidence: 99%